Unix™ Systems Programming: Communication, Concurrency, and Threads - Robbins, Kay; Robbins, Steven (Pearson, 2003)
UNIX Systems Programming: Communication, Concurrency, and Threads by Kay A. Robbins and Steven Robbins UNIX processes, files, and special files Signals and timers POSIX threads, semaphores, and IPC TCP, UDP, multicast, and the Web Features projects on Internet radio, server performance, timers, web caching, and shells Learn how to design and implement reliable UNIX software whether you are using Linux, Solaris, Mac OS X, or another POSIX-based system. This completely updated classic (originally titled Practical UNIX Programming ) demonstrates how to design complex software to get the most from the UNIX operating system. UNIX Systems Programming provides a clear and easy-to-understand introduction to the essentials of UNIX programming. Starting with short code snippets that illustrate how to use system calls, Robbins and Robbins move quickly to hands-on projects that help readers expand their skill levels. This practical guide thoroughly explores communication, concurrency,and multithreading. Known for its comprehensive and lucid explanationsof complicated topics such as signals and concurrency, the bookfeatures practical examples, exercises, reusable code, and simplifiedlibraries for use in network communication applications. A self-contained reference that relies on the latest UNIX standards,UNIX Systems Programming provides thorough coverage of files, signals,semaphores, POSIX threads, and client-server communication. Thisedition features all-new chapters on the Web, UDP, and serverperformance. The sample material has been tested extensively in theclassroom. PRENTICE HALL Professional Technical Reference Upper Saddle River, NJ 07458 www.phptr.com ISBN: 0-13-042411-0.